Forming method of high-temperature-resistant high-thermal-conductivity shell structure

By adopting a double-layer structure of GH4099/CuCrZr in the aircraft engine or rocket thrust chamber, and using additive manufacturing technology and heat treatment, the problems of material overheating and manufacturing process cost at high temperatures are solved, and efficient heat export and performance improvement are achieved.

CN119897465APending Publication Date: 2025-04-29BEIJING HANGXING MACHINERY MFG CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411984194.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The prior art is difficult to effectively connect the radial heterostructure of GH4099 nickel-based high-temperature alloy and CuCrZr alloy at high temperatures, resulting in overheating of the material, reducing performance, and high cost and long cycles of traditional manufacturing processes.

Method used

The GH4099/CuCrZr dual-material double-layer structure is adopted, and composite forming is achieved through additive manufacturing technologies such as laser selection melting, arc additive manufacturing or laser direct deposition, combined with mechanical processing and heat treatment.

Benefits of technology

It overcomes the problem of excellent high temperature strength but low thermal conductivity of GH4099, significantly improves thermal conductivity, solves the processing and manufacturing problems of radial heterostructures, and reduces manufacturing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005222192480000011
    Figure HDA0005222192480000011
  • Figure HDA0005222192480000012
    Figure HDA0005222192480000012
Patent Text Reader

Abstract

The invention provides a forming method of a high-temperature-resistant high-thermal-conductivity shell structure, the high-temperature-resistant high-thermal-conductivity shell structure is a GH4099 / CuCrZr double-material double-layer structural member, the inner layer is made of GH4099 alloy, and the outer layer is made of CuCrZr material; the forming method comprises the steps that if the middle area of the inner layer thickness is provided with a runner or is of an irregular complex structure, a selective laser melting forming method is adopted; if the inner layer is of a structure with a regular and simple shape, an electric arc additive manufacturing or laser direct deposition forming method is adopted; after forming is completed, machining is conducted on the portion, to be formed, of the outer layer on the outer wall face of the inner layer till the requirement for the surface of follow-up forming is met; the outer layer is formed through electric arc additive manufacturing or laser direct deposition with gradually-changed technological parameters.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of advanced manufacturing technology, and particularly relates to a forming method of a high-temperature resistant and high-heat-conductivity shell structure. Background Art

[0002] The inner wall materials of aircraft engines or rocket thrust chambers need to serve for a long time at high temperatures. The inside and outside of the materials are high-temperature gas environments and low-temperature cooling environments respectively. The inside of the combustion chamber reaches more than 1000°C, but the long-term working temperature of GH4099 is only 900°C. In addition, the thermal conductivity of GH4099 is low due to the alloy composition. If the heat cannot be removed, it will cause the material to overheat and burn, causing the material's plasticity, impact toughness, fatigue and high-temperature gas corrosion resistance to decrease, thus causing component failure. GH4099 is a representative of excellent performance at high temperatures, and CuCrZr alloy is a representative of excellent thermal conductivity among copper alloys. The GH4099 / CuCrZr dual-material double-layer structure undoubtedly provides a new idea for this type of component.

[0003] GH4099 nickel-based high-temperature alloy has excellent performance. The forming temperature of high-temperature die forging needs to reach about 1000℃, which will cause deformation, rapid wear and oxidation corrosion of the mold and work surface. If the plate machining method is adopted, for GH4099 alloy, an expensive metal material with high mechanical properties, the tool loss is serious, the machining is difficult, the cycle is long, and the material utilization rate is low, which greatly increases the manufacturing cost. Moreover, the two materials belong to different systems from copper alloys, and the preparation of components of the two materials also brings difficulties to the manufacturing process. The present invention innovatively proposes a GH4099 / CuCrZr dual-material dual-layer structure and the use of additive composite technology to realize the preparation and forming of components. Summary of the invention

[0004] In order to overcome the deficiencies in the prior art, the inventors conducted intensive research and provided a method for forming a high-temperature resistant and high-thermal conductivity shell structure, which solves the problem of large-area connection of radial heterogeneous structures that cannot be achieved by existing traditional technologies, and at the same time solves the problems of high manufacturing costs and long manufacturing cycles of expensive materials.

[0005] The technical solution provided by the present invention is as follows:

[0006] A forming method for a high-temperature resistant and high-thermal conductivity shell structure, wherein the high-temperature resistant and high-thermal conductivity shell structure is a GH4099 / CuCrZr double-material double-layer structure, wherein the inner layer is a CuCrZr alloy and the outer layer is a GH4099 material; the forming method comprises: if the middle area of ​​the inner layer thickness has a flow channel or is an irregular and complex structure, a laser selective melting forming method is adopted; if the inner layer is a structure with a regular and simple shape, an arc additive manufacturing or laser direct deposition forming method is adopted; after the forming is completed, the portion of the outer layer to be formed is mechanically processed on the outer wall surface of the inner layer to meet the surface requirements of subsequent forming; the outer layer is formed by arc additive manufacturing or laser direct deposition with gradual process parameters.

[0007] A forming method of a high temperature resistant and high thermal conductivity shell structure provided by the present invention has the following beneficial effects:

[0008] (1) The present invention provides a forming method for a high-temperature resistant and high-thermal conductivity shell structure, wherein the high-temperature resistant and high-thermal conductivity shell structure is a GH4099 / CuCrZr double-material double-layer structure, wherein the inner layer is a GH4099 alloy and the outer layer is a CuCrZr material, wherein the inner layer has high temperature resistance and high strength, and the outer layer has high thermal conductivity and high strength, thereby overcoming the problem that GH4099 has excellent high-temperature strength but low thermal conductivity and the processing and manufacturing problem of the double-material double-layer structure;

[0009] (2) The present invention provides a forming method for a high temperature resistant and high thermal conductivity shell structure. According to the characteristics of the inner layer structure, arc additive manufacturing / laser direct deposition additive manufacturing / laser selective melting additive manufacturing and other technologies are first used to complete the forming of the inner layer GH4099 material part; secondly, the mechanical processing of the outer layer with CuCrZr is completed to meet the surface requirements of subsequent forming; finally, arc additive manufacturing / laser direct deposition is used to complete the forming of the outer GH4099 material part. After the overall forming is completed, the physical and chemical properties of the two materials are combined to formulate a suitable heat treatment system to achieve the best performance matching; according to the actual product characteristics and structure, selecting a suitable forming method will solve the processing and manufacturing problems of radial heterogeneous material multilayer structural components. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 This is a schematic structural diagram of the GH4099 / CuCrZr dual-material dual-layer structural component in Example 1;

[0011] Figure 2 This is a schematic diagram of the structure of the GH4099 / CuCrZr dual-material dual-layer structural component in Example 2. DETAILED DESCRIPTION

[0012] The following detailed description of the present invention will make the features and advantages of the present invention more clear and explicit.

[0013] The word “exemplary” is used exclusively herein to mean “serving as an example, example, or illustration.” Any embodiment described herein as “exemplary” is not necessarily to be construed as preferred or advantageous over other embodiments.

[0014] Traditional aircraft engines or rocket thrust chambers use GH4099 nickel-based high-temperature alloys, but due to the low thermal conductivity determined by the alloy composition, if the heat cannot be extracted, it is easy to cause the material's plasticity, impact toughness, fatigue and high-temperature gas corrosion resistance to decrease, thereby causing component failure. After research, the present invention considers that GH4099 is a representative of excellent performance at high temperatures, and CuCrZr alloy is a representative of excellent thermal conductivity among copper alloys, and selects GH4099 / CuCrZr double-material double-layer structure to solve the above problems.

[0015] Aircraft engines or rocket thrust chamber products require the inner layer to be heat-resistant and high-strength, and the outer layer to have high thermal conductivity and high strength. Different materials are used for different performance requirements. GH4099 / CuCrZr double-layer material is the preferred material / structure, but the radial heterogeneous material structure cannot be realized by welding or other methods. For GH4099 alloy materials, the forming temperature needs to reach about 1000°C by high-temperature die forging, and there are problems such as deformation, rapid wear and oxidation corrosion of the mold and work surface; if sheet machining is used, for GH4099 alloy, an expensive metal material with high mechanical properties, tool loss is serious, machining is difficult, the cycle is long, and the material utilization rate is low, which greatly increases the manufacturing cost. Traditional manufacturing technology makes it difficult to complete the manufacture of such structural parts.

[0016] Additive manufacturing technology is based on the discrete-deposition principle. It melts metal materials layer by layer through a given heat source, deposits and grows them, and directly forms high-performance structural parts from three-dimensional models. It is an important direction for the development of advanced manufacturing of structural parts in the future. Among them, arc additive manufacturing technology has the characteristics of low equipment cost, stable operation, and high deposition efficiency, and has the advantages of high efficiency and low cost; laser direct deposition forming has the characteristics of high forming accuracy and strong flexibility; laser selective melting forming technology has the characteristics of forming complex structures and excellent performance of prepared components.

[0017] The present invention provides a composite forming method for a GH4099 / CuCrZr dual-material dual-layer structural component. Arc additive / laser direct deposition forming or laser selective melting forming technology is selected according to the characteristics of the inner layer structure, and arc additive / laser direct deposition forming is adopted for the outer layer structure. According to the actual product characteristics and structure, selecting a suitable forming method will solve the processing and manufacturing problems of radial heterogeneous material multi-layer structural components, and at the same time has the potential to reduce manufacturing costs.

[0018] The inner layer of the double-layer structural part is GH4099 alloy, and the outer layer is CuCrZr material. If the middle area of ​​the inner layer has a flow channel or an irregular and complex structure, the laser selective melting forming method is adopted. If the inner layer is a simple structure with a regular shape, arc additive manufacturing or laser direct deposition forming method is adopted. After forming, the part to be formed of the outer layer is machined on the outer wall of the inner layer to meet the surface requirements of subsequent forming. The outer CuCrZr part adopts arc additive manufacturing or laser direct deposition forming with gradual process parameters to achieve high-precision manufacturing. After all additives are completed, a suitable heat treatment system is adopted to achieve the best performance matching.

[0019] The CuCrZr alloy includes the following components in percentage by mass: 0.2% to 0.8% Cr, 0.3% to 0.6% Zr, and the balance is Cu.

[0020] The composite forming method of GH4099 / CuCrZr double-material double-layer structural parts specifically includes the following steps:

[0021] (1) Grind the pure copper substrate flat and wipe it clean with acetone or other solvents, then fix it on the workbench to ensure it is level.

[0022] (2) Select a suitable location on the substrate and deposit the inner layer GH4099 by arc additive manufacturing / laser direct deposition forming / laser selective melting forming.

[0023] When the arc additive manufacturing method is used to form the inner layer, the diameter of the welding wire is 0.8-1.6 mm, such as 1.2 mm, the shielding gas is 90% Ar+8% He+2% CO2, the current is 180-220 A, the wire feeding speed is 8-12 m / min, the welding speed is 5-7 mm / s, and the forming mode is CMT+Pulse.

[0024] When the inner layer is formed by the laser direct deposition forming method, the median particle size of the powder is 53-200 μm, the protective gas is argon, the laser power is 700-900 W, the scanning speed is 8-12 mm / s, and the powder feeding amount is 6-10 g / min.

[0025] When the inner layer is formed by the laser selective melting forming method, the forming parameters include: the median particle size of the powder is 15-60μm, the laser power is 360-380W, the scanning interval is 70-120μm such as 100μm, the welding speed is 400-450mm / s, and a powder cleaning hole with a diameter of not less than 3mm is formed near the substrate to prevent powder from remaining inside during subsequent processing.

[0026] (3) After the inner layer structure is formed, the outer layer to be added is machined. If the outer layer is formed by laser direct deposition, the surface accuracy of the inner layer outer wall after processing is smaller than the powder particle size used for the outer layer laser direct deposition.

[0027] (4) The substrate is clamped on a positioner to ensure that the outer layer to be added is in a horizontal state, mainly to ensure that there is support underneath the molten pool formed by the addition, and the outer layer is formed on the outer wall of the inner layer using an arc additive manufacturing / laser direct deposition forming method.

[0028] When the outer layer is formed by the laser direct deposition forming method, in order to achieve the gradual change of the organization and performance in the transition zone, the method of changing the powder particle size and the laser power is adopted, that is: with the increase of the laser direct deposition height, within the 6mm deposition height (here the deposition height refers to the structural thickness direction), the median particle size of the powder gradually decreases from 200μm to 150μm, the laser power gradually decreases from 5000W to 4000W, the scanning speed is 5-7mm / s, and the powder feeding rate is 4-6g / min.

[0029] When the arc additive forming method is used to form the outer layer, as the laser direct deposition height increases, within a deposition height of 6 mm (the deposition height here refers to the thickness direction of the structure), the shielding gas is 90% Ar + 8% He + 2% CO2, the current is reduced from 200 A to 160 A, the wire feeding speed is 4 to 6 m / min, the scanning speed is 5 to 7 mm / s, and the forming mode is CMT+Pulse.

[0030] When the arc additive manufacturing method forms the inner and outer layers, the shrinkage deformation caused by the high sensitivity of high-temperature alloy deformation to heat is taken into consideration. The arc additive manufacturing process of the main part is completed at one time. Barreled welding wire is used to ensure sufficient welding wire supply, and a chain gas cylinder group is used to ensure sufficient shielding gas source. The shielding gas is a mixed gas of 90% Ar + 8% He + 2% CO2.

[0031] (5) The manufactured double-layer structure is subjected to solution aging heat treatment to complete performance regulation.

[0032] In order to achieve the best matching of performance, the solution treatment system is (1000~1150)℃ / (1~2)h, and the aging system is (400~500)℃ / (1~2)h.

[0033] Example 1

[0034] A forming method for a high-temperature resistant and high-thermal-conductivity shell structure adopts arc additive manufacturing + laser direct deposition to form a GH4099 / CuCrZr double-material double-layer structure.

[0035] The specific implementation method is: the GH4099 / CuCrZr double-material double-layer structure is required to be a hollow cylindrical shell, see Figure 1The outer diameter is 300mm and the wall thickness is 20mm. From the outside to the inside, they are the outer layer of CuCrZr material (Cr 0.6%, Zr 0.5%, and the balance is Cu) and the inner layer of GH4099 material. The thickness of the outer and inner layers are both 10mm and the height is 525mm. Taking into account factors such as manufacturing feasibility, research and production cycle, and comprehensive manufacturing cost, the arc additive manufacturing technology is used to form the inner layer of GH4099 material, and the laser direct deposition is used to form the outer layer of the composite manufacturing solution.

[0036] The raw material used is ф1.6mm GH4099 alloy welding wire. The arc additive manufacturing process parameters were first obtained through experimental exploration: the shielding gas is 90% Ar+8% He+2% CO2, the welding current is 200A, the wire feeding speed is 10m / min, and the welding speed is 6mm / s; under this set of process parameters, the single-pass weld width is 14mm and the height is 1.5mm. The cleaned substrate was polished flat and wiped with acetone, then fixed on the work platform to ensure its level; a suitable position was selected on the substrate to manufacture the inner layer, and the process parameters obtained by exploration were adopted; after the inner layer was manufactured, the outer wall surface of the inner layer to be added with the outer layer was machined, and the surface accuracy of the inner layer outer wall surface after machining was less than the powder particle size used for the outer layer laser direct deposition forming; the outer layer was formed by using laser direct deposition technology with a gradual process parameter change method. With the increase of the laser direct deposition height, within the 6mm deposition height, the median particle size of the powder gradually decreased from 200μm to 150μm, the laser power gradually decreased from 5000W to 4000W, the scanning speed was 5mm / s, and the powder feeding rate was 5g / min.

[0037] The manufactured double-layer structure is subjected to solution aging heat treatment to complete the performance regulation. The solution treatment system is 1100℃ / 1.5h and the aging system is 450℃ / 2h.

[0038] The thermal conductivity of the formed dual-material dual-layer structure is more than 5 times higher than that of the GH4099 high-temperature alloy with the same thickness. At the same time, the thickness of the dual-layer structure can be adjusted to improve the thermal conductivity.

[0039] Example 2

[0040] A forming method for a high-temperature resistant and high-thermal-conductivity shell structure adopts laser selective melting forming + laser direct deposition to form a GH4099 / CuCrZr double-material double-layer structure.

[0041] The specific implementation method is: the GH4099 / CuCrZr double-material double-layer structure is required to be a variable diameter hollow shell, see Figure 2The inner layer has a flow channel in the middle area, the maximum outer diameter is 300mm, the wall thickness is 20mm, and from the outside to the inside are the outer layer of CuCrZr material (Cr 0.6%, Zr 0.5%, and the balance is Cu) and the inner layer of GH4099 material. The thickness of the outer and inner layers are both 12mm and the height is 556mm. Taking into account factors such as manufacturing feasibility, research and development cycle, and comprehensive manufacturing cost, the composite manufacturing solution of laser selective melting to form the inner layer GH4099 material part and laser direct deposition to form the outer layer material part was finally selected.

[0042] The raw materials used are 50μm GH4099 alloy powder, laser power 360W, scanning spacing 100μm, and scanning speed 450mm / s. The cleaned substrate is polished flat and wiped clean with acetone, then fixed on the work platform to ensure its level; a suitable position is selected on the substrate for manufacturing the inner layer, and the process parameters obtained by exploration are adopted; after the inner layer is manufactured, the outer wall surface of the inner layer to be added is machined, and the surface accuracy of the inner layer outer wall after processing is less than the powder particle size used for laser direct deposition forming of the outer layer; the outer layer is formed by using laser direct deposition technology and a process method with gradual process parameters. With the increase of laser direct deposition height, within the 6mm deposition height, the median particle size of the powder gradually decreases from 200μm to 150μm, the laser power gradually decreases from 5000W to 4000W, the scanning speed is 5mm / s, and the powder feeding rate is 5g / min.

[0043] The manufactured double-layer structure is subjected to solution aging heat treatment to complete the performance regulation. The solution treatment system is 1100℃ / 1.5h and the aging system is 450℃ / 2h.

[0044] The thermal conductivity of the formed dual-material dual-layer structure is more than 5 times higher than that of the GH4099 high-temperature alloy with the same thickness. At the same time, the thickness of the dual-layer structure can be adjusted to improve the thermal conductivity.

[0045] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.

[0046] The contents not described in detail in the specification of the present invention belong to the common knowledge of those skilled in the art.

Claims

1. A method for forming a high temperature resistant and high thermal conductivity shell structure, characterized in that: The high temperature resistant and high thermal conductivity shell structure is a GH4099 / CuCrZr double-material double-layer structural part, the inner layer is GH4099 alloy, and the outer layer is CuCrZr material; the forming method includes: if the middle area of ​​the inner layer thickness has a flow channel or is an irregular and complex structure, a laser selective melting forming method is adopted; if the inner layer is a structure with a regular and simple shape, an arc additive manufacturing or laser direct deposition forming method is adopted; after the forming is completed, the part of the outer layer to be formed on the outer wall surface of the inner layer is mechanically processed to meet the surface requirements of subsequent forming; the outer layer is formed by arc additive manufacturing or laser direct deposition with gradual process parameters.

2. The forming method of the high temperature resistant and high thermal conductivity shell structure according to claim 1, characterized in that: The CuCrZr alloy comprises the following components in percentage by mass: 0.2% to 0.8% Cr, 0.3% to 0.6% Zr, and the balance is Cu.

3. The forming method of the high temperature resistant and high thermal conductivity shell structure according to claim 1, characterized in that: The forming method specifically comprises the following steps: The inner layer is formed on the substrate by arc additive manufacturing / laser direct deposition forming / laser selective melting forming method; After the inner layer structure is formed, the outer layer to be added is machined on the inner layer outer wall surface; The outer layer is formed on the outer wall of the inner layer by using arc additive manufacturing / laser direct deposition forming method; The manufactured double-layer structure is subjected to solution aging heat treatment to complete performance regulation.

4. The forming method of the high temperature resistant and high thermal conductivity shell structure according to claim 3, characterized in that: When the inner layer is formed by the arc additive manufacturing method, the diameter of the welding wire is 0.8-1.6 mm, such as 1.2 mm, the shielding gas is 90% Ar+8% He+2% CO2, the current is 180-220 A, the wire feeding speed is 8-12 m / min, and the welding speed is 5-7 mm / s.

5. The forming method of the high temperature resistant and high thermal conductivity housing structure according to claim 3, characterized in that: When the inner layer is formed by laser direct deposition forming method, the median particle size of the powder is 53-200 μm, the protective gas is argon, the laser power is 700-900 W, the scanning speed is 8-12 mm / s, and the powder feeding amount is 6-10 g / min.

6. The forming method of the high temperature resistant and high thermal conductivity shell structure according to claim 3, characterized in that: When the inner layer is formed by the laser selective melting forming method, the laser power is 360-380W, the scanning interval is 70-120μm, and the scanning speed is 400-450mm / s.

7. The forming method of the high temperature resistant and high thermal conductivity housing structure according to claim 3, characterized in that: If the outer layer is formed by laser direct deposition, the surface accuracy of the outer wall of the inner layer after processing is smaller than the powder particle size used for laser direct deposition forming of the outer layer.

8. The forming method of the high temperature resistant and high thermal conductivity shell structure according to claim 3, characterized in that: When the outer layer is formed by the laser direct deposition forming method, as the laser direct deposition height increases, within a deposition height of 6 mm, the median particle size of the powder gradually decreases from 200 μm to 150 μm, the laser power gradually decreases from 5000 W to 4000 W, the scanning speed is 5 to 7 mm / s, and the powder feeding rate is 4 to 6 g / min; when the deposition height exceeds 6 mm, the parameters of the laser direct deposition forming method remain unchanged.

9. The forming method of the high temperature resistant and high thermal conductivity housing structure according to claim 3, characterized in that: When the arc additive forming method is used to form the outer layer, as the height of laser direct deposition increases, within a deposition height of 6 mm, the shielding gas is 90% Ar + 8% He + 2% CO2, the current is reduced from 200 A to 160 A, the wire feeding speed is 4 to 6 m / min, and the scanning speed is 5 to 7 mm / s.

10. The forming method of the high temperature resistant and high thermal conductivity housing structure according to claim 3, characterized in that: When the double-layer structure is subjected to solution-aging heat treatment, the solution temperature is (1000-1150)°C / (1-2)h, and the aging temperature is (400-500)°C / (1-2)h.